Childhood life events and their relationship with post-traumatic stress disorder in adults in Metropolitan Lima. - Portella, Christian (2022)
Objectives: To determine the relationship between childhood life events and PTSD in adult population of Metropolitan Lima. Materials and methods: A secondary analysis was carried out of the Epidemiological Study of Mental Health of Metropolitan Lima 2 012, which used the instruments of a short and modified version of the Egna Minen av Bardoms Uppfostran (EMBU), a questionnaire on early adverse events, and the Mini Internacional Neuropsychiatric Interview (MINI), Spanish version. Results: Those who received a more permissive upbringing being allowed to do activities that their siblings were not, presented a statistically significant relationship with PTSD (OR 1.70, 95% CI 1.09-2.65, p = 0.019), the same as those who experienced adverse life events or were the object of or had suffered blackmail, manipulations or humiliations (OR 6.22, 95% CI 4.11-9.42, p<0.001). Conclusions: There is a relationship between permissive parenting style (“They allowed him to do things that his siblings were not allowed to do”), and the experience of childhood adverse events (“While growing up, he was subjected to (or suffered) from frequent blackmail, manipulation or humiliations)” with PTSD, in adults from Metropolitan Lima.